Application of wireless networks in the course of the organization and intelligence telecommunication systems - Бурячок, Володимир Леонідович (Ukrainian Information Security Research Journal, 2013)
Uncontrolled distribution and use of information and cyber space has gradually led to a significant complication of problems finding information warring parties in the open and getting it in a relatively open and closed electronic sources to each other and to protect their own information resources from unauthorized cybernetic influence. The solution of such problems is impossible without building now an overwhelming majority of the world's own systems cyber security, and the development and introduction of new, more effective methods and methods of intelligence information and telecommunication (IT) systems. First of all, this is due to the continuous growth of information that circulates is stored and processed in the information and cyberspace these countries, the need to protect such information from the influence of internal and external cyber threats and interventions, the rapid development of new IT technologies and global computerization. With this in mind, the article discussed the purpose and the main varieties of intelligence information and telecommunication systems. Proposed definition of intelligence in telecommunication systems (1ST). Defines the scope of the possible interests of the 1ST and the method of its conduct, and place of the 1ST in the overall process of getting information. An example of the use of wireless technologies during the execution of the tasks of exploration of the 1ST.